Histone H2A Nuclear/Cytoplasmic Trafficking Is Essential for Negative Regulation of Antiviral Immune Response and Lysosomal Degradation of TBK1 and IRF3 - Wu, Xiao Man; Fang, Hong; Zhang, Jie; Bi, Yong Hong; Chang, Ming Xian (Frontiers in Immunology, 2021)
Histone H2A is a nuclear molecule tightly associated in the form of the nucleosome. Our previous studies demonstrated the antibacterial property of piscine H2A variants against gram-negative bacteria Edwardsiella piscicida and Gram-positive bacteria Streptococcus agalactiae. In this study, we show the function and mechanism of piscine H2A in the negative regulation of RLR signaling pathway and host innate immune response against SVCV infection. SVCV infection significantly inhibits the expression of histone H2A during an early stage of infection, but induces the expression of histone H2A during the late stage of infection such as at 48 and 72 hpi. Under normal physiological conditions, histone H2A is nuclear-localized. However, SVCV infection promotes the migration of histone H2A from the nucleus to the cytoplasm. The in vivo studies revealed that histone H2A overexpression led to the increased expression of SVCV gene and decreased survival rate. The overexpression of histone H2A also significantly impaired the expression levels of those genes involved in RLR antiviral signaling pathway. Furthermore, histone H2A targeted TBK1 and IRF3 to promote their protein degradation via the lysosomal pathway and impair the formation of TBK1-IRF3 functional complex. Importantly, histone H2A completely abolished TBK1-mediated antiviral activity and enormously impaired the protein expression of IRF3, especially nuclear IRF3. Further analysis demonstrated that the inhibition of histone H2A nuclear/cytoplasmic trafficking could relieve the protein degradation of TBK1 and IRF3, and blocked the negative regulation of histone H2A on the SVCV infection. Collectively, our results suggest that histone H2A nuclear/cytoplasmic trafficking is essential for negative regulation of RLR signaling pathway and antiviral immune response in response to SVCV infection.